Bibliometric evaluation of Anais Brasileiros de Dermatologia (2013-2022) - Miot, Hélio Amante [UNESP] (2024)
The Anais Brasileiros de Dermatologia, published since 1925, is the most influential dermatological journal in Latin America, indexed in the main international bibliographic databases, and occupies the 50th position among the 70 dermatological journals indexed in the Journal of Citations Reports, in 2022. In this article, the authors present a critical analysis of its trajectory in the last decade and compare its main bibliometric indices with Brazilian medical and international dermatological journals. The journal showed consistent growth in different bibliometric indices, which indicates a successful editorial policy and greater visibility in the international scientific community, attracting foreign authors. The increases in citations received (4.1×) and in the Article Influence Score (2.9×) were more prominent than those of the main Brazilian medical and international dermatological journals. The success of Anais Brasileiros de Dermatologia in the international scientific scenario depends on an assertive editorial policy, on promptly publication of high-quality articles, and on institutional stimulus to encourage clinical research in dermatology.